Mata Pencaharian Berkelanjutan: Kajian Ekonomi Hasil Hutan Bukan Kayu Pada Hutan Rakyat Di Desa Buntoi Kalimantan Tengah: Sustainable Livelihood: Economic Study Of Non-Timber Forest Product in Community Forest in Buntoi Village Central Kalimantan - Afentina, Afentina; Dulamin, Jumri; Sigalingging, Nico Fransiskus; Indrayanti, Lies; Yanarita, Yanarita (HUTAN TROPIKA, 2025)
Community forests are one of sustainable development strategies that provides a variety of environmental services, especially to meet subsistence needs and provide community income. The important value of community forests can be seen from the contribution of non-timber forest products (NTFPs) to community's income. Therefore, it is important to conduct studies to create programs for the development of community forests. This research aims to identify various types of NTFPs in the Buntoi Village Community Forest, Central Kalimantan and their economic contribution to community income. This research uses a case study approach by combining qualitative and quantitative methods. Data was collected through field observations and interviews with respondents selected purposively. This research found 14 types of NTFPs and a contribution of Rp. 29,247,097/year/respondent or Rp. 2,437,258/respondent/month. The conclusion that can be drawn is that community forests are able to provide a significant contribution to income so they need to be developed further so that they can support increased community welfare.